Reforma Agraria y productividad - Schaller, Sven (2007)
This paper argues that the underlying model ofmost development scholars 10 address the problem ofrural poverty is inappropriate. The reason is seen in the fact (11mthe changes in the production system ofa hacienda-dominated to a capitalist agriculture are not cetcris paribus but rather deteriorare from the perspective offarmers dile lo the high transaction costs, higher prices ofinputs. the farmers ' insufficient knowledge and educatiou. the /I).\'.') oI distrtbution networkss. and the denied access ro credits. Thercfore. tlie implcnientation ofa land reforni breaking up the hacienda svstem ami instulling a sector of minifundistas does not lead romore output, higher productivitv, more occupation and higher incomes for the poor in the agrarian sector.